Strengthening Religious Moderation in University: Initiation to Universitas Islam Negeri Alauddin Makassar - Abdul Syatar (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2020)
Students, educators, and education staff who do not understand the totality of the essence and urgency of religious moderation in the scope of UIN Alauddin Makassar are essential issues. The rooted religious moderation is one of the Chancellors' thoughts that has been actualized by the Moderation House's declaration. This study aims to initiate a strategy for UIN Alauddin Makassar College in strengthening religious moderation in the academic community. This research is qualitative research located at UIN Alauddin Makassar using a socio-cultural approach. The idea generated from this research is a Road Map of Moderation, which is integrated into the Tridarma of Higher Education, such as a curriculum that contains religious moderation, moderation-based research assistance, and others.